Emergency department malnutrition screening and support model improves outcomes in a pilot randomised controlled trial. Issue 3 (5th November 2013) - Vivanti, A; Isenring, E; Baumann, S; Powrie, D; O'Neill, M; Clark, D; Courtice, S; Campbell, K; Ferguson, M
Abstract : Objective: To trial malnutrition screening in older adults presenting to an emergency department (ED) and compare two service delivery models of nutritional support on nutritional status, quality of life, falls and unplanned hospital admissions. Design: Participants (>60 years) presenting to ED screened at malnutrition risk were randomly allocated to either the control group (receiving regular treatment from community hospital interface programme nursing staff) or intervention group (receiving dietetic assessment, nutrition intervention and follow-up in addition to regular community hospital interface programme support). Outcome measures including body weight, quality of life, depression, falls history and days of hospital admissions were collected at baseline and 12 weeks. Results: Of 703 patients screened, 84 (12%) were identified at malnutrition risk. 24 consented to the intervention study, with 88% (21/24) confirmed to be malnourished. Clinically important but not statistically significant differences were found over the 12-week trial; the intervention group (n=9) gained 0.8 kg (±3.7) while the control group (n=10) lost −1.1 kg (±4.6). The intervention group also had better quality of life, less depression and shorter hospital admissions. Conclusions: Malnutrition screening appears feasible in ED. This pilot suggests a model of care providing nutrition support to older adults identified at nutritional risk may lead to improved patient outcomes but further research in a larger sample is required to confirm these findings.